2005
DOI: 10.1111/j.1551-2916.2005.00326.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Segregation at Grain Boundaries on Deformation of B, C‐Doped Silicon Carbides at Elevated Temperatures

Abstract: The effect of oxygen segregation at grain boundaries on the deformation of 1 wt% boron (B)‐ and carbon (C)‐doped β‐silicon carbide (B, C‐doped SiC) was investigated by compression testing at 2073 K. We studied the deformation of sinter‐forged B, C‐doped SiC (sinter‐forged SiC), which contained the minimum amount (0.07 wt%) of oxygen as an impurity, and that of hot isostatically pressed B, C‐doped SiC (HIPed SiC), which contained 1 wt% oxygen. Oxygen was detected at grain boundary in HIPed SiC by energy‐dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Thus gas partial pressure is increased and may be locally near the equilibrium partial pressure. Such effect of high mechanical pressure on the reaction hindering were also noticed by Vassen [36] and Shinoda [38] for SiC sintered by HIP (with degassing before 1450 • C). The same conclusion was envisaged in a recent work where decarbonation of rhodochrosite and kutnahorite species sintered under high pressure by SPS was restrained [39].…”
Section: Discussion On Sintering Parameters Effectmentioning
confidence: 67%
See 1 more Smart Citation
“…Thus gas partial pressure is increased and may be locally near the equilibrium partial pressure. Such effect of high mechanical pressure on the reaction hindering were also noticed by Vassen [36] and Shinoda [38] for SiC sintered by HIP (with degassing before 1450 • C). The same conclusion was envisaged in a recent work where decarbonation of rhodochrosite and kutnahorite species sintered under high pressure by SPS was restrained [39].…”
Section: Discussion On Sintering Parameters Effectmentioning
confidence: 67%
“…Thus carbon, which is located in between the grains, drastically affects hardness far beyond a simple effect of porosity. Several authors [38,44,45] studied the importance and the strong effect of hetero-elements/additives elements like B/C, Al, Al 2 O 3 or SiO 2 on mechanical properties but experiments with carbon only are rarely seen. Raczka et al have observed a decrease of hardness for SiC samples with C excess between 1 and 6 wt% and explained it by the increase of the soft carbon phase in SiC sample.…”
Section: Effect Of Carbon Impurity On Densification and Mechanical Bementioning
confidence: 98%
“…Shinoda [5] studied the effect of boron doping on compression deformation of SiC, and showed that the grain-boundary diffusion coefficient was increased with increasing amount of boron segregation at grain boundaries. Ohtsuka and co-workers [6] reported the effect of cosegregation of both boron and oxygen at grain-boundary on deformation of SiC, and suggested that the cosegregation accelerated grain-boundary diffusion further. * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Shinoda et al [87] studied the effect of boron doping on compression deformation of SiC, and showed that the grain-boundary diffusion coefficient was increased with increasing amount of boron segregation at grain boundaries. Ohtsuka et al [88] reported the effect of co-segregation of both boron and oxygen at grain-boundary on deformation of SiC, and suggested that the co-segregation accelerated grain-boundary diffusion further. The temperature dependence of the strength of hot pressed SiC containing B additions had been measured by Prochazka and Charies [89].…”
Section: Structure-mechanical Properties Relationsmentioning
confidence: 99%